Transformações musicais na Igreja Assembleia de Deus: a transição da hinologia tradicional ao pop pentecostal na década de 1990 - Guimarães, Jairo Manhães (2019)
This text has as an objective to problematize the main changes in the Brazilian gospel scenario from the “Assembleia de Deus” church. What were the main changes that occurred in the 90’s that transformed the gospel music? To treat this question, we’ll take as an empirical example the career of the pastor and singer Cassiane, arguing that her musical style – the “Pop pentecostal” – was responsible for considerable changes in the Pentecostal music scenario and beyond it.